2023
DOI: 10.1002/csr.2480
|View full text |Cite
|
Sign up to set email alerts
|

Corporate environmental responsibility in polluting firms: Does digital transformation matter?

Abstract: The motivations for firms to undertake corporate environmental responsibility (CER) have been a hot topic in academia. However, with the rise of the digital economy, it is still been determined whether digital transformation will become a driving force for firms to assume CER. Based on panel data of Chinese listed firms in polluting industries, this article empirically tests whether and how digital transformation affects CER. The results show that digital transformation significantly motivates firms to assume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 56 publications
2
2
0
1
Order By: Relevance
“…In this sense, our results demonstrate the role of sustainability disclosure mechanisms as an intangible resource within a substantive approach that improves corporate legitimacy, promotes stakeholder interaction and reduces the market myopia effect. In line with Lin et al (2021), our findings show that participation in a sustainability rating can reduce information asymmetry in financial markets and enhance pricing accuracy. Moreover, our results contribute to previous literature evidencing that the lower mispricing found in a sustainability disclosure context is linked to a long-term focus on future earnings.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this sense, our results demonstrate the role of sustainability disclosure mechanisms as an intangible resource within a substantive approach that improves corporate legitimacy, promotes stakeholder interaction and reduces the market myopia effect. In line with Lin et al (2021), our findings show that participation in a sustainability rating can reduce information asymmetry in financial markets and enhance pricing accuracy. Moreover, our results contribute to previous literature evidencing that the lower mispricing found in a sustainability disclosure context is linked to a long-term focus on future earnings.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, the results confirm hypothesis 1, in that the market myopia effect is lower in high sustainability reporters (HSR) than in low sustainability reporters (LSR). The results confirm previous evidence on the existence of market myopia (Del Río & Santamaria, 2016;Matos & Coelho, 2016) as well as being in line with Lin et al (2021), who proposed that information asymmetries could be reduced by sustainability disclosure mechanisms.…”
Section: Descriptive Statistics Market Myopia and Persistencesupporting
confidence: 91%
See 1 more Smart Citation
“…Referring to existing studies, the logarithm of word frequency associated with digitalization in corporate annual reports +1 is used to quantify DT (Lin & Xie, 2023; Lin & Zhang, 2023; Zhai et al, 2022), and the re‐estimated result is shown in Column (2). Meanwhile, we gauge the DT levels of firms using digital intangible assets presented in corporate annual reports (Li, Rao, & Wan, 2022), and the re‐estimated result is summarized in Column (3).…”
Section: Resultsmentioning
confidence: 99%
“…(3) 数据的智能化分析和决策支持。数字技术 可以为资源环境管理提供智能化分析和决策支持 [53] 。 基于长期监测的资源环境数据, 使用大数据、 机器 学习等数字技术手段实现对资源利用和环境管理 过程的智能化分析和预测, 分析结果为管理者的科 学决策提供支撑。 (4) 信息共享和协同工作。数字技术可以促进 信息的共享和协同 [54] 。通过建立资源环境的数智化 平台和云计算系统, 实现数据的共享、 交换和整合, 步探究 [56,57] 。其次, 生态环境保护并不意味着经济 的负增长, 社会经济发展如何促进资源开发与环境 保护的协同, 两者之间存在怎样的耦合关联, 均需 要进一步梳理 [58] 。最后, 全球可持续发展目标进程 严重受阻, 有半数可持续发展具体目标出现中度或 严重偏离预期, 超过 30% 的具体目标与 2015 年相比 毫无进展, 一些脆弱地区的可持续发展目标甚至出 现倒退 [59,60] 能机制与智慧协同管理路径 [66] 。此外, 还需要考虑 中国数字技术需求的迅猛增长对电力能源需求及 碳排放的潜在影响。有研究指出, 人工智能技术具 有双重属性, 其广泛应用可能导致对能源需求的增 加 [67] 。目前随着 ChatGPT 的发展, 以大模型为代表 的生成式人工智能 (AIGC) 对算力需求的持续增长 可能引致新的环境不公平问题 (算力供给与需求存 在错位) [68] , 二者之间的关系尚需深入探究。…”
Section: 用效果。unclassified